GOLFIG Chemo-Immunotherapy in Metastatic Colorectal Cancer Patients. A Critical Review on a Long-Lasting Follow-Up - Caraglia, Michele; Correale, Pierpaolo; Giannicola, Rocco; Staropoli, Nicoletta; Botta, Cirino; Pastina, Pierpaolo; Nesci, Antonello; Caporlingua, Nadia; Francini, Edoardo; Ridolfi, Laura; Mini, Enrico; Roviello, Giandomenico; et al. (Frontiers in Oncology, 2019)
Background: GOLFIG is a chemo-immunotherapy regimen established in preclinical models which combines gemcitabine + FOLFOX poly-chemotherapy with low dose s.c. recombinant interleukin-2 (rIL-2) and granulocyte-macrophage Colony Stimulating Factor (GM-CSF). Promising antitumor effects in mCRC patients were obtained in previous Phase II and III trials. Here we report the results of fifteen years of follow up. Methods: This is a multi-institutional retrospective analysis including 179 mCRC patients receiving GOLFIG regimen between June 2002 and June 2018. Sixty-two of them received the treatment as front-line (enrolled in the GOLFIG-2 phase III trial) and 117 as second/third line (49 enrolled in the GOLFIG-1 phase II trial and 68 as compassionate use). One-hundred twelve patients showed a primary left side and 67 a primary right side; K/N-ras mutational status was available in 74 cases and an activating mutation was detected in 33. Kaplan-Meier and Cox-regression analyses were carried out to relate PFS and OS with different parameters. Results: On the overall, we recorded a mean PFS and OS of 15.28 [95%CI:10,36-20,20] and 24.6 [95%CI:19,07-30,14] months, respectively, with 14 patients surviving free of progression for ten years. This regimen, in our updated survey of the GOLFIG-2 trial, confirmed superiority over FOLFOX in term of PFS (HR= 0.58 p=0.006) with a trend to a longer OS (HR=0.69, P=0.06) in the first line. Our analysis also confirmed significant antitumor activity in pre-treated patients reporting a mean PFS and OS of 12.55 [95%CI:7.19-17.9] and 20.28 [95%CI:14.4-26.13] months, respectively. IrAEs were recorded in 24% of the cases and were related to a longer survival (HR=0.36; P=0.0001). Finally, patients’ outcome was not correlated to sex, sidedness and MT-K/N-ras. Conclusions: GOLFIG regimen is a reliable underestimated therapeutic option in pre-treated mCRC patients and offers a strong rationale to design further trials.